2011
DOI: 10.1007/s00415-011-6038-5
|View full text |Cite
|
Sign up to set email alerts
|

White matter involvement in idiopathic normal pressure hydrocephalus: a voxel-based diffusion tensor imaging study

Abstract: The aim of this study was to characterise the white matter damage involved in idiopathic normal pressure hydrocephalus (INPH) using diffusion tensor imaging (DTI) and the relationship between this damage and clinical presentation. Twenty patients with INPH, 20 patients with Alzheimer's disease and 20 patients with idiopathic Parkinson's disease (as disease control groups) were enrolled in this study. Mean diffusivity (MD) and fractional anisotropy (FA) were determined using DTI, and these measures were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 42 publications
4
84
0
Order By: Relevance
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%
“…MR tractography has been recommended as a means of differentiating among NPH, AD, and PD. 36,38,40,47,50,52,65,66,76 Hydrocephalus studies have suggested that the compression indicated by high fractional anisotropy (FA) levels will eventually cause the neuronal degeneration, brain edema, or deterioration of the white matter indicated by low FA levels.…”
Section: Periventricular Tracts In Hydrocephalusmentioning
confidence: 99%
“…To better inform clinical practice, comparative studies including these neural disorders is needed. 20) Third, this study did not further analyze the relationships between FA values and the effects of the tap test. Although the Japanese Guidelines for INPH (2004) stipulate criteria, their validity and reliability have yet to be established.…”
Section: Dti Of Inphmentioning
confidence: 96%
“…6,9,20,22,27) DTI can sensitively detect the direction of diffusion of water molecules and so reveals the orientation of the white matter tracts. 36) This anatomical detail enables clinically useful characterization of the degeneration of neural fibers affected by various neural diseases.…”
Section: Dti Of Inphmentioning
confidence: 99%
See 1 more Smart Citation